The prostaglandin E2/EP4 receptor/cyclic AMP/T-type Ca2+ channel pathway mediates neuritogenesis in sensory neuron-like ND7/23 cells - Kenji Mitani; Fumiko Sekiguchi; Takashi Maeda; Yukari Tanaka; Shigeru Yoshida; Atsufumi Kawabata (Journal of Pharmacological Sciences, 2016)
We investigated mechanisms for the neuritogenesis caused by prostaglandin E2 (PGE2) or intracellular cyclic AMP (cAMP) in sensory neuron-like ND7/23 cells. PGE2 caused neuritogenesis, an effect abolished by an EP4 receptor antagonist or inhibitors of adenylyl cyclase (AC) or protein kinase A (PKA) and mimicked by the AC activator forskolin, dibutyryl cAMP (db-cAMP), and selective activators of PKA or Epac. ND7/23 cells expressed both Cav3.1 and Cav3.2 T-type Ca2+ channels (T-channels). The neuritogenesis induced by db-cAMP or PGE2 was abolished by T-channel blockers. T-channels were functionally upregulated by db-cAMP. The PGE2/EP4/cAMP/T-channel pathway thus appears to mediate neuritogenesis in sensory neurons.